Bark Essential Oil of Cedrelopsis grevei from Madagascar: Investigation of Steam‐Distillation Conditions. Issue 2 (February 2014) - Rakotobe, Miarantsoa; Menut, Chantal; Andrianoelisoa, Hanitriniaina Sahondra; Rahajanirina, Voninavoko; Tsy, Jean Michel Leong Pock; Rakotoarimanana, Vonjison; Ramavovololona, Perle; Danthu, Pascal
Abstract The effect of the distillation time on the yield and chemical composition of the bark essential oil of Cedrelopsis greveiBaill. was investigated. Distillation kinetics were determined for three batches of bark sampled from two sites, i.e., Itampolo (batches IT1 and IT2) and Salary (SAL), located in a region in the south of Madagascar with characteristically large populations of C. grevei. The bark samples were subjected to steam distillation, and the essential oil was collected at 3‐h intervals. The total yield (calculated after 14 h of distillation) varied from 0.9 to 1.7%, according to the batch tested. Moreover, the essential oils obtained were characterized by GC‐FID and GC/MS analyses. During the course of the distillation, the relative percentages of the most volatile components (monoterpenes and sesquiterpene hydrocarbons) diminished progressively, whereas the least volatile ones (oxygenated derivatives) increased at a consistent rate. Principal component analysis (PCA) and agglomerative hierarchical clustering analysis (AHC) of the results, performed on 13 principal components, allowed distinguishing three chemical groups, corresponding to the three batches, irrespective of the distillation time. This indicated that the chemical variability currently observed with commercial samples is not mainly linked to the experimental conditions of the extraction process, as the distillation time did not significantly alter the chemical composition of the essential oils.